The impact of globalisation on the traditional concept of nation state - Ahmad, Nehaluddin (2014)
The purpose of this paper is to look at a few of the ways that the globalisation process has affected the institution of the nation-state, in particular its ability to autonomously manage its own social and economic policies. Although the nationstate as an institution will not die out in the near future because of globalisation process but its control of power has been greatly undermined, and its hold on populations has been significantly minimized.The nation-state has become just one of several world organisational structures.Sovereignty - presuming such a thing ever really existed in the past.I shall attempt to place globalisational impacts upon the nation-state, national sovereignty, and culture, and the implications of these impacts upon the nation-state of the future.